Sdq-Sdr Topological Map of Surface Topographies - Czifra, Árpád; Barányi, István (Frontiers in Mechanical Engineering, 2020)
The reliable characterization of surface topographies – especially in case of tribological processes – requires complex and comprehensive solution methods. The use of a combination of roughness parameters offers effective solutions in many cases. In our study, we found a close correlation between the Sdq-Sdr parameter pair and we applied the two parameters as a topological map. Surface topographies resulting from different machining techniques (turned, milled, ground, honed, electric discharge machined, and sintered) were placed in the topological map and their possibilities of use were explored. It was established that surfaces with an orientation characteristically have lower Sdq-Sdr value pairs than non-oriented or multi-oriented surfaces; however, surface defects, injuries and machining discrepancies increase the values of Sdq-Sdr parameters. Then the Sdq-Sdr topological map was applied for worn surfaces resulting from abrasive and tribochemical processes, and it was established that the worn surfaces examined are characterized by small Sdq-Sdr values. Test results showed that in case of manufacturing processes, the topological map is suitable for identifying manufacturing discrepancies and manufacturing defects, and it highlights structural changes in the microgeometry in the course of the wear process.